2021
DOI: 10.1111/mec.15945
|View full text |Cite
|
Sign up to set email alerts
|

Comparable response of wild rodent gut microbiome to anthropogenic habitat contamination

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 94 publications
(190 reference statements)
1
23
0
Order By: Relevance
“…The analysis by Antwis et al (2021) potentially examines the response of Apodemus mice to medium and high absorbed dose rates but does not examine how exposure to radionuclides per se impacts the gut microbiota in different species of rodent. By contrast, comparable impacts of exposure to radionuclides in the gut microbiota of three (out of four) species of Apodemus are apparent in samples collected from the CEZ and the Fukushima accident sites (Lavrinienko, Hämäläinen, et al, 2021).…”
Section: Differences Between Microbiota Detected In Samples From Faec...mentioning
confidence: 99%
“…The analysis by Antwis et al (2021) potentially examines the response of Apodemus mice to medium and high absorbed dose rates but does not examine how exposure to radionuclides per se impacts the gut microbiota in different species of rodent. By contrast, comparable impacts of exposure to radionuclides in the gut microbiota of three (out of four) species of Apodemus are apparent in samples collected from the CEZ and the Fukushima accident sites (Lavrinienko, Hämäläinen, et al, 2021).…”
Section: Differences Between Microbiota Detected In Samples From Faec...mentioning
confidence: 99%
“…On the other hand, gut bacteria can have complicated effects on host inflammatory immune responses, both in the gut and other tissues ( Ichinohe et al, 2011 ; Hooper, Littman & Macpherson, 2012 ; Wilks & Golovkina, 2012 ; Shukla et al, 2017 ; Lazar et al, 2018 ; Kogut, Lee & Santin, 2020 ), making the effects of commensal gut bacteria on host responses to infections difficult to predict. As anthropogenic impacts on wildlife and their bacterial communities increase in extent, via antibiotics and other stressors ( Kelly et al, 2014 ; Teyssier et al, 2018 ; Trevelline et al, 2019 ; Kraemer, Ramachandran & Perron, 2019 ; Lavrinienko et al, 2021 ), a better understanding of the importance of bacterial communities in wildlife hosts is imperative to prepare for, and predict, effects of emerging wildlife diseases.…”
Section: Introductionmentioning
confidence: 99%
“…One other group has undertaken a number of studies on the small mammal gut microbiome for animals in Chornobyl and, latterly, Fukushima (e.g. Lavrinienko et al, 2020; Lavrinienko, Hämäläinen, et al, 2021; Lavrinienko, Mappes, et al, 2018; Lavrinienko, Tukalenko, et al, 2018). Their studies have consistently identified associations between radiation and a response within the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a number of studies on the impact of radiation on microbiomes within 'natural laboratories', such as the Chornobyl and Fukushima exclusion zones (e.g. Antwis et al, 2021;Lavrinienko, Hämäläinen, et al, 2021;Newbold et al, 2019;Videvall et al, 2022).…”
Section: Introductionmentioning
confidence: 99%